Multipath traffic splitting algorithm based on adaptive granularity - Peng WANG; Ju-long LAN; Shu-qiao CHEN (Tongxin xuebao)
Aiming at the dilemma between load balancing and packet reordering in multipath routing,an adaptive dynamic multipath traffic splitting(ADTS) algorithm was proposed.The algorithm classified Internet flows into two categories:the aggressive and the normal through analyzing the characters of the traffic,and applies different splitting granularities to the two classes of flows based on the idea of differentiated service.The theoretical analysis and simulation results show that ADTS algorithm reduces the number of reordering packets while has better performance of load balancing.